A comparative study of ZrS2-based thin film solar cells using the SCAPS solar cell capacitance simulator. (12th January 2023) - Gupta, Shubhra; Shishodia, Gayatri; Shishodia, P K
Abstract: Transition metal chalcogenides have been studied for their potential applications in optoelectronic devices such as light emitting diodes, solar cells, photodetectors, field-effect transistors, etc. Their unique structural and versatile electronic and optical properties, non-toxic chemical nature and abundance are some of the features that have attracted tremendous attention from researchers. In this study, optimised junctions formed between zirconium sulphide (ZrS2 ) and copper zinc tin sulphide (CZTS), copper indium sulphide, copper indium selenide and cadmium telluride absorber layers have been explored and compared using SCAPS (a solar cell capacitance simulator program) for photovoltaic applications. The impact of operating temperature, illumination intensity, series and shunt resistances on cell performance has been discussed in detail. Comparative study concluded that the Al-ZnO/ZrS2 /CZTS structure presents the best efficiency of 9.72% at room temperature. Other performance parameters obtained are short circuit current density J sc = 25.16 mA cm −2, open circuit voltage V oc = 0.61 and fill factor FF = 68.86%. The external quantum efficiency response was examined under the AM1.5 spectrum for different device models. The simulation results suggest that n -ZrS2 can be used as an excellent buffer layer to fabricate environmentally friendly non-toxic solar cells.